2019
DOI: 10.1186/s40478-019-0667-9
|View full text |Cite
|
Sign up to set email alerts
|

Microglia pre-activation and neurodegeneration precipitate neuroinflammation without exacerbating tissue injury in experimental autoimmune encephalomyelitis

Abstract: Human inflammatory or neurodegenerative diseases, such as progressive multiple sclerosis (MS), occur on a background of age-related microglia activation and iron accumulation as well as pre-existing neurodegeneration. Most experimental models for CNS diseases, however, are induced in rodents, which are naturally characterized by a homeostatic microglia phenotype, low cellular iron load and absence of neurodegeneration. Here, we show that naïve LEWzizi rats – Lewis rats with a zitter rat background – show a spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…As we have shown previously, iron levels in ageing LEWzizi rats increase more pronouncedly compared with age-matched wild-type Lewis rats (32). Here, we deepen the topographical analyses of CNS iron accumulation ( Figure 3A-C).…”
Section: Iron Abnormally Accumulates In Oligodendrocytes Axonal Trsupporting
confidence: 75%
See 2 more Smart Citations
“…As we have shown previously, iron levels in ageing LEWzizi rats increase more pronouncedly compared with age-matched wild-type Lewis rats (32). Here, we deepen the topographical analyses of CNS iron accumulation ( Figure 3A-C).…”
Section: Iron Abnormally Accumulates In Oligodendrocytes Axonal Trsupporting
confidence: 75%
“…The role of iron as an amplifier of tissue damage has gained increasing interest in various neurological diseases (41); however, the translatability of experimental rodent data to neuroinflammation and neurodegeneration in the human CNS is limited (29). In the current work, we characterised iron accumulation in the brain of LEWzizi rats, which descend from zitter (zi/zi) rats (30,31) and present with abnormally high iron levels in the CNS (32). There, iron accumulates with age mainly in oligodendrocytes and myelin sheaths in a similar anatomical and cellular distribution as observed in aged humans (29,32).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Currently, TSPO PET imaging is the most widely used in vivo method for inferring on the status of microglial activation. Direct evidence for an innate inflammatory response in AD was described nearly 20 years ago 70 , and subsequent studies have demonstrated neuroinflammation in PD 71 , ALS 72 , 73 , MS 74 , major depressive disorder (MDD) 30 , obsessive compulsive disorder (OCD) 75 and a growing number of other nervous system pathologies. Previous studies in rodents after lipopolysaccharide (LPS) or toxins have also reported that dramatic upregulation of TSPO levels are correlated with microglial activation in response to brain injury or neuroinflammation 76 , 77 although in postmortem investigations in humans both activated microglia and astroglia may overexpress TSPO 27 , 28 .…”
Section: Tspo In the Brainmentioning
confidence: 99%
“…Neither of these conditions had an effect on EAE related inflammation nor on the neurodegenerative process due to the pre‐existing microglia activation (Rubino et al, ). In a further study, EAE was induced by active immunization or passive T‐cell transfer in an experimental model, which was characterized by microglia activation, accelerated iron accumulation in the brain, and progressive neurodegeneration (Wimmer et al, ), a pathological scenario which closely reflects the tissue changes seen in the progressive stage of multiple sclerosis (Mahad, Trapp, & Lassmann, ). Also in this model, the pathology of EAE was not modified by the pre‐existing microglia activation, nor was the progressive neurodegenerative phenotype altered by the inflammatory process of EAE.…”
Section: Microglia and Macrophages In Inflammatory Diseases Of Rodentsmentioning
confidence: 99%